ChemInform Abstract: Synthesis of Chiral 3‐Substituted 1, 3, 4, 5‐Tetrahydro‐1, 4‐benzodiazepin‐2‐ones via a Domino Copper‐Catalyzed SN2/Coupling Reaction. Issue 15 (24th March 2016) - Lu, Dongming; Ma, Chang; Yuan, Shuai; Zhou, Lihong; Zeng, Qingle
Abstract: First, the reaction of 2‐iodobenzyl bromide (Ia) with various (S)‐amino acids is investigated to produce the desired benzodiazepine structures.